Developing a techno-economic framework for national-level end-state decarbonisation resource analysis: a UK application - Gao, Lin; Naylor, Philip; Hegab, Abdelrahman; Pilidis, Pericles (MDPI, 2026)
Amid growing urgency for net-zero delivery and calls for simplified energy system modelling, this study presents a techno-economic framework, termed “End-state Decarbonisation Resource Analysis” (EDRA), for evaluating national decarbonisation strategies. EDRA integrates demand estimation, technology replacement, generation calculation and economic assessment, and employs scenario modelling and optimisation to estimates the technical, geographical, and financial resources required for full national decarbonisation. The framework offers a simplified yet comprehensive approach for national energy system assessment. Applied to the UK, EDRA reveals substantial gaps between current government capacity targets and the requirements of a fully decarbonised system aligned with the UK’s policy goals of net-zero, energy independence and energy security. Meeting these aims would require more than triple the nuclear target, over double the offshore wind target, more than 400 GW of electrolysers, combined cycle hydrogen turbines and electricity grid, ~50 thousand km2 of land for wind and solar, and trillion-pound scale investment. Delivering this scale of resource deployment within 25 years presents a significant policy challenge. Nevertheless, the results demonstrate clear advantages of a decarbonised electrification system over fossil fuel-based alternatives. A key policy recommendation is to prioritise demand reduction to ease generation resource pressure.
This article belongs to the Special Issue Energy Transition: Interaction of Gas/Hydrogen and Electricity Systems
Keywords: 40 Engineering; 7 Affordable and Clean Energy; 33 Built environment and design; 51 Physical sciences; energy system modelling; decarbonisation; energy policy; energy demand; renewables; nuclear; hydrogen; energy storage